Towards an Inclusive Climate Governance System: Indigenous Knowledge and State Policy Synergies in Rural Zimbabwe - Shingirai Mugambiwa; Ambo Upe (International Journal of Qualitative Research, 2026)
Climate governance in rural Zimbabwe confronts multifaceted challenges as communities grapple with intensifying climate impacts, namely irregular rainfall and extended droughts, each of which undermines livelihood security, agricultural output, and food availability. This paper examines the synergies between IKS and state climate policies in the Mutoko District, illuminating the transfer of indigenous wisdom across agricultural planning, ceremonial observances, and adaptive practices. The paper employed an exploratory qualitative framework anchored in participatory inquiry and grounded theory. Data was gathered through in-depth interviews, focus group dialogues, and key informant interviews with a diverse sample of farmers, elders, traditional leaders, and extension officers. Thematic analysis was employed to analyze data, and the findings established that traditions such as rainmaking ceremonies and the veneration of ancestors cultivate social unity and validate the authority of indigenous governance, while youth-led collectives increasingly intertwine traditional ecological wisdom with mobile and digital media, generating hybrid frameworks that elevate adaptive capacity. The analysis therefore articulates that an authentically inclusive climate governance framework in Zimbabwe necessitates the formal legitimization of Indigenous Knowledge Systems, the establishment of deliberative platforms that facilitate co-learning, and sustained, directed investments in educational initiatives that ensure cultural and technical continuity across generations. The research concludes that addressing epistemic divisiveness and integrating participatory, culturally relevant governance procedures in semi-arid rural areas is essential for enhancing resilience and supporting the communities impacted.